TMOD-14. CONJOINED CLASS I AND II EPITOPES ENHANCE NEOANTIGEN-TARGETED ACTIVE IMMUNOTHERAPY. (12th November 2021) - Swartz, Adam; Congdon, Kendra; Nair, Smita; Li, Qi-Jing; Herndon, James; Suryadevara, Carter; Riccione, Katherine; Reedy, Jessica; Cook, Sarah; Archer, Gary; Norberg, Pam; Sanchez-Perez, Luis; et al.
Abstract: INTRODUCTION: Cancer vaccines involve the administration of tumor-associated antigens into the host to generate anti-tumor T cell responses. Glioblastoma (GBM) is a disease with poor prognosis. GBM has a limited number of immunotherapeutic targets due to low mutational load, and is also highly heterogeneous; targeting a single antigen leads to antigen escape and tumor growth. METHODS: VMDK mice were subcutaneously implanted with 750, 000 SMA560 cells and on days 1 and 8 post implantation, mice were treated with 15 nmol of the universal helper epitope, P30, conjoined to the MHCI-restricted neoepitopes Odc1 MHCI-P30 or Topbp1 MHCI-P30 . Human CD27 (hCD27) transgenic mice were intracranially implanted with CT2A-Odc1, followed by anti-CD27 and 15 nmol of Odc1 MHCI-P30 . B16.OVA or B16.F10 tumor cells were intracranially implanted in hCD27 mice and received SIINFEKL-P30 or Trp2-P30 conjoined peptides. Tumor growth, survival, or IFNγ secretion of splenic or tumor-infiltrating cells was assessed. RESULTS: Unlike Odc1 MHCI mixed with P30, conjoined Odc1 MHCI-P30 had equivalent immunogenicity and anti-tumor efficacy to that observed with native long Odc1 peptide. Native long peptide of Topbp1 did not elicit an antitumor response, yet Topbp1 MHCI-P30 caused an increase in numbers of IFNγ-secreting splenocytes and a decrease in tumor growth and similar to that seen with Odc1 MHCI-P30 . Anti-CD27 treatment significantly increased numbers of IFNγ secreting splenocytes in Odc1 MHCI-P30 vaccinated hCD27 mice, and the use of anti-CD27 with Odc1 MHCI-P30 achieved long-term survival in 90% of tumor bearing hCD27 mice. Anti-CD27 synergized with SIINFEKL-P30 and Trp2-P30 to significantly improve survival after administration of these peptides. CONCLUSIONS: Our work shows that poorly immunogenic neoantigens can be conjoined to P30 and used to generate an anti-tumor response in mouse models of GBM, and anti-tumor responses of conjoined peptides can be enhanced with anti-CD27 treatment. Together, these data demonstrate the efficacy of neoantigen vaccines for the treatment of heterogeneous GBM.